2018
DOI: 10.1161/cir.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Projected Costs of Informal Caregiving for Cardiovascular Disease: 2015 to 2035: A Policy Statement From the American Heart Association

Abstract: INTRODUCTION:In a recent report, the American Heart Association estimated that medical costs and productivity losses of cardiovascular disease (CVD) are expected to grow from $555 billion in 2015 to $1.1 trillion in 2035. Although the burden is significant, the estimate does not include the costs of family, informal, or unpaid caregiving provided to patients with CVD. In this analysis, we estimated projections of costs of informal caregiving attributable to CVD for 2015 to 2035. METHODS:We used data from the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
130
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(135 citation statements)
references
References 103 publications
(156 reference statements)
0
130
0
5
Order By: Relevance
“…Data on the national economic burden of CVD in the other mega-countries were collected from a included series of studies and reports [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Beginning with countries of a low and middle HDI, data of projected economic losses due to CVD in India between 2012 and 2030 were identified in a study Evidence of CVD economic impact for mega-countries with a very high HDI were identified in seven sources.…”
Section: Literature Searchmentioning
confidence: 99%
“…Data on the national economic burden of CVD in the other mega-countries were collected from a included series of studies and reports [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Beginning with countries of a low and middle HDI, data of projected economic losses due to CVD in India between 2012 and 2030 were identified in a study Evidence of CVD economic impact for mega-countries with a very high HDI were identified in seven sources.…”
Section: Literature Searchmentioning
confidence: 99%
“…Parallel to the high prevalence and vast number of deaths, CAD also places a crushing economic burden. According to the recent American Heart Association report, the medical costs and productivity losses of CVD are expected to grow from $555 billion in 2015 to $1.1 trillion in 2035 (Dunbar et al, 2018;Benjamin et al, 2019). Although CAD has become a major concern in global public health, there still a long way to fully understand the etiology of CAD before getting it under control.…”
Section: Introductionmentioning
confidence: 99%
“…This person presents specific and different care needs, such as physical help (moving to the bathroom, to the bed); communication (verbal and nonverbal cues to other family members when the patient has aphasia); support for eating, taking care of their personal hygiene and emotional support (dealing with the destructive behavior caused by the consequences of the disease) (4) . The many tasks that are attributed to the family caregiver, lack of support, unpreparedness to care, the level of dependence of the patient, the chronicity of the disabling situation, the complexity of the care activities, the worsening of health status and the uncertainty of future causes burden, and this may lead to social isolation, reduction or end of leisure activities, impairment of professional activity, loss of job and lack of time for self-care (5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%